2016
DOI: 10.1016/j.ijlp.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents as perpetrators of aggression within the family

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Within all obtained data sets, there was a clear pattern of males being more likely to perpetrate AVTP than females, with approximately 60% of offenders being male. This finding is consistent with some of the research internationally in the area of AVTP (Calvete et al., 2015; Ibabe et al, 2014; Kuay et al., 2016; Miles & Condry, 2014; Nock & Kazdin, 2002). Both NSW and Victoria showed that females were more likely to be perpetrators of AVTP at a younger age than their male counterparts, with it seeming a problematic behavior that they “age out of,” a phenomenon that is not mirrored by male AVTP offenders.…”
Section: Discussionsupporting
confidence: 91%
“…Within all obtained data sets, there was a clear pattern of males being more likely to perpetrate AVTP than females, with approximately 60% of offenders being male. This finding is consistent with some of the research internationally in the area of AVTP (Calvete et al., 2015; Ibabe et al, 2014; Kuay et al., 2016; Miles & Condry, 2014; Nock & Kazdin, 2002). Both NSW and Victoria showed that females were more likely to be perpetrators of AVTP at a younger age than their male counterparts, with it seeming a problematic behavior that they “age out of,” a phenomenon that is not mirrored by male AVTP offenders.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 20 identified studies, most were conducted in the USA (n ¼ 7) or in Spain (n ¼ 9), with two studies conducted in Canada and one in the UK. Sample sizes ranged from 50 (Kuay et al, 2016) to 2,213 (Brezina, 1999) and most (75 percent) of the studies had been published in the last six years. A number of studies explored a large number of variables as potential characteristics associated with AVTP; therefore, this review only considers the major characteristics identified (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 14 of the studies described the gender of perpetrators of AVTP. Four studies (Calvete, Orue and Gámez-Guadix, 2015;Calvete, Orue, Gamez-Guadix and Bushman, 2015;Ibabe et al, 2014;Kuay et al, 2016;Nock and Kazdin, 2002) identified gender as a key characteristic, finding that males were more likely to perpetrate AVTP. Ten other studies, however, concluded that AVTP was a non-gendered phenomenon.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…As for the characteristics of adolescents involved in APV, no significant gender differences were observed. In general, there is no consensus in the literature regarding differences between boys and girls in exercising APV (Moulds and Day, 2017), with some studies reporting males perpetrate more violence than females (Ibabe et al, 2014;Calvete et al, 2015;Kuay et al, 2016), whereas others studies found no genders differences (Calvete et al, 2014;Margolin and Baucom, 2014;Bartle-Haring et al, 2015). The lack of consensus is associated to the type of samples employed, judicial or normalized.…”
Section: Discussionmentioning
confidence: 99%